An Assessment of Teeth Cleaning Practices In 12- And 15-Year-Old School Going Children in Rural Areas of Sanwer Block of District Indore, Madhya Pradesh - Singh, Varsha; Deshpande, Ajit R; Wavare, Rajshekher (National Journal of Community Medicine, 2014)
Introduction: Oral health is an essential component of health throughout life. Practices of oral hyegine built up in childhood. The present study was undertaken to assess the teeth cleaning practices of school going children. Methods: A questionnaire was prepared to assess the teeth cleaning practices among the study subjects. After the pilot study was conducted on 86 eligible students, the sample size was determined to be 1400 students among a total of 3600 students of the 30 schools selected for study. Of the selected schools standard 7th and 10th students sufficed the age criteria. The sample was obtained by selecting the students randomly to cover the minimally required sample size as per the inclusion and the exclusion criteria. Result & Conclusion: Assessment of oral hygiene practices of the study population revealed that majority of the population (65%) used to clean their teeth once daily using toothbrush and toothpaste in a horizontal motion, the distribution of habit being similar across both age groups and gender in the government schools, implying an overall great defect in practicing recommended methods and techniques of cleaning teeth.